Germline variants of base excision repair genes and breast cancer: A polymorphism in DNA polymerase gamma modifies gene expression and breast cancer risk - Popanda, Odilia; Seibold, Petra; Nikolov, Ivaylo; Oakes, Christopher C.; Burwinkel, Barbara; Hausmann, Sebastian; Flesch‐Janys, Dieter; Plass, Christoph; Chang‐Claude, Jenny; Schmezer, Peter (International journal of cancer, 2013)
Base excision repair (BER) removes DNA damage induced by endogenous reactive oxygen species or ionizing radiation, important breast cancer risk factors. Genetic variation associated with impaired BER might thus increase breast cancer risk. Therefore, we assessed risk associations of 123 common single nucleotide polymorphisms (SNPs) in 19 BER genes in 1,639 postmenopausal breast cancer cases and 1,967 controls from the German population‐based case‐control study MARIE. SNPs were tagging SNPs representing genetic variation across the gene together with potentially functional SNPs. Risk associations were assessed using conditional logistic regression, adjusted for potential breast cancer risk factors. Significant associations between polymorphisms and breast cancer risk were found for one SNP in PARP2 and three SNPs in the mitochondrial DNA polymerase gamma, POLG. A SNP in the promoter region of POLG (rs2856268, A>G) showed a protective effect for homozygous GG carriers (odds ratio 0.81, 95% confidence intervals 0.65–1.00). Joint analysis of an enlarged sample set and haplotype analysis supported the results for POLG. Quantification of POLG mRNA expression in lymphocytes of 148 breast cancer patients revealed higher mRNA levels for rs2856268 GG carriers (p value = 0.038). A luciferase promoter assay showed significant differences between constructs harboring the respective alleles. Taken together, our results suggest that genetic variation in the POLG promoter region affects DNA polymerase gamma levels in mitochondria. This could contribute to the reported increase in mitochondrial mutation frequency resulting in dysfunction and altered breast cancer risk. Risk effects and the functional impact of the POLG promoter variant require further confirmation. What's new? Systematic screening of base excision repair genes led to the identification of breast cancer risk‐modifying variations in the DNA polymerase gamma gene (POLG). Three of these variations were associated with reduced risk. Further analysis revealed that mRNA levels of one of the protective POLG variants were elevated in lymphocytes from breast cancer patients. Because polymerase gamma localizes to mitochondria, the findings raise important questions concerning a molecular link between breast carcinogenesis and mitochondrial function.